The Role of Mesenchymal Stem Cells and Exosomes in Tumor Development and Targeted Antitumor Therapies - Enguang Yang; Suoshi Jing; Yuhan Wang; Hanzhang Wang; Ronald Rodriguez; Zhiping Wang (Hindawi Limited, 2023)
Mesenchymal stem cells (MSCs) can be isolated from various tissues in adults and differentiated into cells of the osteoblasts, adipocytes, chondrocytes, and myocytes. Recruitments of MSCs towards tumors have a crucial contribution to tumor development. However, the role of MSCs in the tumor microenvironment is uncertain. In addition, due to its tropism to the tumor and low immunogenic properties, more and more pieces of evidence indicate that MSCs may be an ideal carrier for antitumor biologics such as cytokines, chemotherapeutic agents, and oncolytic viruses. Here, we review the existing knowledge on the anti- and protumorigenic effect of MSCs and their extracellular vesicles and exosomes, the role of MSCs, and their extracellular vesicles and exosomes as antitumor vectors.